2010
DOI: 10.1021/jp104419k
|View full text |Cite
|
Sign up to set email alerts
|

Ether-Bond-Containing Ionic Liquids and the Relevance of the Ether Bond Position to Transport Properties

Abstract: The ionic liquids (ILs) 1-ethoxyethyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide, [EtO(CH(2))(2)MMI][Tf(2)N], and N-(ethoxyethyl)-N-methylmorpholinium bis(trifluoromethanesulfonyl)imide, [EtO(CH(2))(2)MMor][Tf(2)N] were synthesized, and relevant properties, such as thermal stability, density, viscosity, electrochemical behavior, ionic conductivity, and self-diffusion coefficients for both ionic species, were measured and compared with those of their alkyl counterparts, 1-n-butyl-2,3-dimethylimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 29 publications
(58 reference statements)
5
78
0
2
Order By: Relevance
“…Another excellent example was illustrated by Donato et al [ 50 ] as: [Me(OCH 2 CH 2 ) 3 25 °C). The same conductivity increase trend was observed for ether-functionalized ILs based on imidazolium cations [ 38 ], pyrrolidinium, piperidinium, oxazolidinium, or morpholinium cations [ 24 ], phosphonium and ammonium cations [ 25 , 51 , 52 ], as well as guanidinium cations [ 53 , 54 ]. Belhocine et al [ 55 ] prepared a series of seven-member ring azepanium-based ILs (Scheme 8.1 ) and found the incorporation of alkoxyalkyl group results in a reduction in viscosities and an increase in conductivities.…”
Section: Electrochemical Propertiessupporting
confidence: 60%
“…Another excellent example was illustrated by Donato et al [ 50 ] as: [Me(OCH 2 CH 2 ) 3 25 °C). The same conductivity increase trend was observed for ether-functionalized ILs based on imidazolium cations [ 38 ], pyrrolidinium, piperidinium, oxazolidinium, or morpholinium cations [ 24 ], phosphonium and ammonium cations [ 25 , 51 , 52 ], as well as guanidinium cations [ 53 , 54 ]. Belhocine et al [ 55 ] prepared a series of seven-member ring azepanium-based ILs (Scheme 8.1 ) and found the incorporation of alkoxyalkyl group results in a reduction in viscosities and an increase in conductivities.…”
Section: Electrochemical Propertiessupporting
confidence: 60%
“…[176] However,t here are some major challenges concerning the utilization of ILs for lithium battery applications, such as their relativelyl ower ionic conductivity at ambient temperature compared with organic-solvent-based electrolytes and, in some cases,t heir incompatibility with commonly employed active materials, such as graphite. Very promising resultst argeting the improvement in lithium-ion transport and an enhanced compatibilityw ith standard electrode materials were obtained, among other things, by mixing different ILs; [178][179][180][181] adding functional organic compounds (e.g.,V C, EC, or chloroethylene carbonate); [179,[182][183][184][185][186][187] or designing functionalized ILs, including asymmetricala nions [101,[188][189][190][191][192][193] or ether/ester groups, [101,[194][195][196][197] as well as cyano groups. [198] The incorporation of an oxygen atom into the aliphatic side chain, for instance, resultedi nasignificantly decreased melting temperature and enhanced ionic conductivity, which was attributed to reduced crystal packing of the ions.…”
Section: Il-based Electrolytesmentioning
confidence: 99%
“…20 The physical properties of ILs, in particular the viscosity/conductivity, can be altered through the inclusion of ether linkages in the alkyl side chains of cations . 33 It has been proposed that the inclusion of ether bonds results in increased specific capacitances in EDLCs using mesoporous carbon electrodes by adding a degree of flexibility into the anion and alteration of the charge density. 34 Therefore to explore As a substantial number of reports have shown that the pore characteristics of electrodes strongly influence the performance of EDLCs, 22,28,[35][36][37][38] we also compare 30 the behaviour of these ILs when combined with electrodes of differing average pore size (d) in the small mesopore range (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…23 Viscosities determined for each of the ILs in this work are given in Table 1 33,34 ). Electron donation from the oxygen atom diminishes the charge of the cation resulting in weaker anion-cation interactions.…”
mentioning
confidence: 99%